Childhood Adversity, Addiction Severity, and Comorbidity Among Patients Receiving Opioid Use Disorder Treatment: The Role of Emotion Regulation. Issue 2 (13th February 2023) - Carr, Meagan M.; Ellis, Jennifer D.; Saules, Karen K.; Ledgerwood, David M.
Abstract: Patients in opioid use disorder (OUD) treatment report high rates of childhood adversity, and women experience greater exposure to certain types of childhood adversity ( e.g., sexual abuse). Childhood adversity is associated with clinical severity, but the mechanisms explaining this association are not well understood. Participants ( N = 171) in opioid agonist treatment completed measures of childhood adversity, emotion regulation, and clinical severity ( i.e., addictive behaviors, depression, and anxiety). Women endorsed greater childhood adversity and higher current psychopathology than men. The association between childhood adversity and clinical severity varied as a function of symptom type, although emotion regulation was a strong predictor in all models. Women reported higher levels of anxiety after controlling for covariates, childhood adversity, and emotion dysregulation. Future research should investigate treatment strategies to address emotion dysregulation among patients in OUD treatment, particularly women who may present with greater childhood adversity exposure and anxiety.